Vying for the control of inflammasomes: the cytosolic frontier of enteric bacterial pathogen - host interactions - Sanchez,Garrido J; Slater,SL; Clements,A; Shenoy,A; Frankel,G (Cellular Microbiology, 2020)
Enteric pathogen-host interactions occur at multiple interfaces,includingthe intestinal epitheliumand deeper organsof the immune system. Microbial ligands and activities are detected by host sensorsthat elicit a range of immune responses. Membrane-bound Toll-Like Receptors (TLRs) and cytosolic inflammasomepathways are key signal transducers that trigger production of pro-inflammatory molecules such as cytokines and chemokinesand regulate cell deathin response to infection. In recent years, the inflammasomes have emerged as a key frontier in the tusslebetween bacterial pathogens and the host. Inflammasomes are complexes that activate caspase-1and are regulated by related caspases, such as caspase-11, -4, -5 and -8.Importantly, enteric bacterial pathogens can actively engage or evade inflammasome signalling systems. Extracellular, vacuolar and cytosolic bacteria have developed divergent strategies to subvert inflammasomes. While some pathogens take advantage of inflammasomeactivation(e.g. Listeria monocytogenes, Helicobacter pylori), others(e.g. E. coli, Salmonella, Shigella, Yersinia sp.) deploy a range of virulence factors, mainly type 3 secretion system (T3SS) effectors, that subvert or inhibit inflammasomes. In this review we focus on inflammasomepathwaysand their immune functions and discuss how enteric bacterial pathogens interact with them.These studies have not only shed light on the inflammasome-mediated immunity, but also the exciting area of mammalian cytosolic immune